Ankle Temporizing External Fixation as a Risk for Sharp Exposure: A Common Occurrence. Issue 4 (November 2022) - Swords, Michael P.; Patel, Jay; Kane, Kevin
Category: Trauma; Ankle Introduction/Purpose: External fixation is a common initial management strategy for complex ankle injuries. The purpose of this study was to evaluate external fixation frame constructs for risk of sharp exposure to the health care team at the receiving institution when patients were received in transfer for definitive care after an external fixator was applied at an outside institution. Methods: Patients with an ankle external fixator applied prior to transfer to the senior author over a 3 year period were included. Injuries represented- included pilon fractures, complex ankle fractures and other injuries with significant soft tissue swelling. External fixation constructs were evaluated for sharp pin ends when the patient was received in transfer. Frame constructs were assessed for pins that were cut resulting in sharp ends or pins that were never cut, resulting in an exposed sharp pin end. The location of sharp pins was recorded as a tibial shaft pin, foot pin, or calcaneal pin. calcaneal pins were recorded as either monolateral or transcalcaneal. Results: 39 patients with ankle external fixation were received in transfer by the senior author over a 3- year period. 16/39 external fixation constructs had sharp pins that presented potential for injury at the receiving institution. Of the external fixation constructs with sharp pin ends 2/16 had tibial pins that were cut in a manner that resulted in a sharp pin end. 14/16 of the external fixation frames with sharp pin ends exposed were transcalcaneal pins where the leading sharp point was not cut after the pin was inserted through the calcaneus and the external fixator was assembled. No foot pins or monolateral calcaneal pins resulted in sharp pin ends. Conclusion: External fixation plays an important role in staged management of complex ankle injuries. All external fixation pins should be cut in a manner that results in blunt pin ends to reduce potential for injury to all members of the health care team. Pin cutters that result in blunt pin ends are commercially available and should be used to prevent potential sharp injury in all external fixation cases